Study of the nonlinear optical properties of 4-nitroaniline type compounds by density functional theory calculations: Towards new NLO materials (2018)
In the present work, the values of dipolar moment, linear polarizability, first hyperpolarizability, energies of electronic hyperconjugation, and HOMO-LUMO gaps were determined for investigate the nonlinear optical properties of 18 4-nitroaniline type compounds. For this purpose, the finite field approximation and the Natural Bond Orbital method were used, performing the electronic calculations at the DFT level using the chemical model B3LYP/6-311++G(d,p). The NBO analysis revealed the occurrence of multiple interactions by orbital overlap involving strong intramolecular charge transfer, which is believed to contribute to the NLO activity of the nitro-aniline type derivatives. The properties calculated in this work suggest that several of the studied compounds could exhibit better NLO properties than the reference materials (urea, KDP and 2M4NA), which leads to the possibility of considering some of the compounds studied here as candidates to be experimentally tested in applications such as laser devices and materials for optical information processing. © 2018